AN ANALYSIS OF POLITENESS STRATEGIES USED BY CLAIRE PETERSON IN THE BOY NEXT DOOR MOVIE - Supriyanta Supriyanta; Imam Ghozali (JELLT (Journal of English Language and Language Teaching), 2017)
In social interaction, people need to be aware of othersâ€™ faces to consider their feelings or maintain the relationship. In order to save a personâ€™s face, people are supposed to use politeness strategies. The objective of the paper is to describe the types and functions of politeness strategies used by Claire Peterson in The Boy Next Door movie. This research belongs to discourse analysis and uses the theory of politeness strategies proposed by Brown and Levinson. The data is movie script of The Boy Next Door movie which is in the form of words and utterances. Based on the analysis, there are 37 utterances containing politeness strategies used by Claire Peterson. In detail, she uses the strategy of bald on record seven times or 18.9%, positive politeness 20 times or 54%, negative politeness 9 times or 24.4%, and off record once or 2.7%. The most frequent politeness strategy used by Claire Peterson is â€œoffer and promiseâ€ which belongs to positive politeness strategy. This strategy is used 7 times or 18.9%. In general, she uses politeness strategies to maintain and build good relationship with the others in her daily life.